PROVIDING ADEQUATE INFORMATION FOR OUTPATIENTS IN RSUPN DR. CIPTO MANGUNKUSUMO JAKARTA NOVEMBER 2018 - FEBRUARY 2019 - Tantri Puspa Ditya; Adang Bachtiar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Long waiting time in medical services can cause by excess patient capacity, insufficient hospital staff and resources, and long registration process. This problem common happens in hospital in Indonesia, including RSUPN Dr. Cipto Mangunkusumo, Jakarta. In 2017, the average time for waiting to get medical services in RSUPN Dr. Cipto Mangunkusumo was more than 60 minutes. However, the standard of waiting time is less than or equal to 60 minutes. Long waiting time can affect to the patient services and satisfaction. This study aims to examine the effectiveness of providing information at each service points with waiting time at RSUPN Dr. Cipto Mangunkusumo. Methods: This study was a quantitative study with cross-sectional design. Quick Win/ Electronic Health Record recapitulation was used to measure the waiting time to get medical services from registration until met the doctor for each patient. The sample was 1130 patients. The sample in this study was patient who had been recorded in electronic medical record during July 2018 to February 2019. The data analyzed in univariate and bivariate analysis used Chi-square. Results: There was association between providing information at each service points with patient waiting time (95% CI, p= 0.042). After implemented the information of how long-time services needed at each service points, the average time for patient waited has decreased 3 minutes from 120.5 minutes to 117.5 minutes. Conclusion: Providing information at each service points associated with decreasing waiting time for patient. The hospital should increase the performance of health providers and give the appreciation to the polyclinic or department that can achieve the standard of waiting time. Hopefully, giving a honor to the health providers can motivating them to give better health services to the patient and reduce the waiting time. Keywords: Patient services, waiting time, information on patient service time